Hyperrealism as an Artistic Phenomenon in French Literature of the 20th-21st Centuries - Savchuk, Ruslana Ivanivna; Tuchkova, Olena Oleksandrivna (Journal of History Culture and Art Research, 2020)
The article deals with the concept of hyperrealism in the projection on a fictional work of the 20th-21st centuries. The study is focused on the features and techniques of hyperrealism, inherent in different types of art, which have been reflected in literature, in particular French literature. The period of powerful development of digital technologies made scientists wonder about the essence of reality, and taking into account the fact that the latter can create their own reality, their attitude towards it acquires different, modified features: what I see may be or may not be reality. Thus, the dominant philosophy of this period is the attempt to manipulate reality in various forms of art, both verbal and fine art. Hyperrealism in painting, sculpture, and cinema uses similar techniques. Therefore, the purpose of this article is to find out the techniques and means of hyperrealism in the French literature of the 20th-21st centuries. Works of French writers whose creativity is consonant with the techniques of creating/reproducing excessive reality in a literary text were selected as the illustrative base of the research. The methods of component and linguostylistic analysis, as well as elements of communicative-pragmatic and descriptive analyzes were applied to achieve the desired objective. Thus, in the article the narrative technique of detailing the image is positioned as the dominant technique of hyperrealism in French prose works, functioning at the compositional, linguistic, and syntactic levels of the literary text. It is found out that this technique is accompanied by a detailed description of the photograph as a reflection of the development of photorealism precisely in this period and by a realistic description of the city acquiring forms of working with the map. Detailing that runs through the whole content and structure of a fictional work of art is aimed at the reader, in particular at gaining his/her confidence in the events and/or actions depicted. Herewith, the text has a minimum of evaluative characteristics that could simulate the reader’s opinion regarding events and/or actions, since all the detailing is directed to the free judgment of the reader. Therefore, the detail is the key element by which you can "grab" the reality, because changing the detail gives rise to a new spiral of reality. The content of the article can serve for further studies of modifications of the concept of reality, its dependence on the worldview of a man, and its multidimensionality on the material of works of fiction or other arts from the perspective of psycho or sociolinguistics.